THE ROLE OF THE CONSTRUCTIVIST LEARNING CYCLE STRATEGY IN THE TEACHING PROCESS - Mohammed, Khemmad; khalifa smail, Ben; Djilali, Mezaini (International Journal of Psychosocial Rehabilitation, 2022)
Over the past two decades, educational research has seen major transformations in the educational process by researchers. This shift from questioning the external factors affecting learning, such as teacher variables, raises questions about what is going on in the learner’s mind such as his previous knowledge and ability to handle information, and patterns of thinking, and among the theories that interested in this structural theory. Several educational strategies have emerged from this theory, including the learning cycle strategy. The learning cycle is a teaching model that can be used by the teacher in classroom teaching as a teaching strategy. It emphasizes the interaction between the teacher and the learner during the educational situation and depends on the scientific activities. Through this paper we will try to address this strategy from the beginning of its origin and then the definition and characteristics and to address the five stages in detail, and then the role of both the teacher and learner in this strategy, and how to plan teaching Through it.